2022
DOI: 10.1002/hed.27023
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery for the identification of unknown primary head and neck squamous cell carcinomas: Its effect on the wait and the weight

Abstract: Background Neck carcinoma of unknown primary (CUP) is a frequent scenario. Transoral robotic mucosectomies (TORM) of pharynx have increased rate of primary identification, but come with cost of treatment delay. Methods We reviewed patients who underwent CUP protocol from 2014 to 2020. Patients with cervical nodes carcinoma and failure to localize a primary source were classified as CUP. We determined primary identification rate and postoperative complications. Results We included 65 patients underwent TORM. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In our survey, both non-TORS and TORS head and neck surgeons reported similar overall indication outcomes. Precisely, most head and neck surgeon participants considered sleep apnea-related base of tongue surgery and cT1-T2 oropharyngeal and supraglottic cancers as the most appropriate indications of TORS, which match with the most accepted indications in the literature [ 6 , 16 , 17 , 18 , 19 ]. However, notably, European non-TORS and TORS head and neck surgeons appear to be less familiar with fewer common indications, e.g., Sistrunk procedure, laryngocele excision, nasopharyngeal cancer, or thyroid surgery [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our survey, both non-TORS and TORS head and neck surgeons reported similar overall indication outcomes. Precisely, most head and neck surgeon participants considered sleep apnea-related base of tongue surgery and cT1-T2 oropharyngeal and supraglottic cancers as the most appropriate indications of TORS, which match with the most accepted indications in the literature [ 6 , 16 , 17 , 18 , 19 ]. However, notably, European non-TORS and TORS head and neck surgeons appear to be less familiar with fewer common indications, e.g., Sistrunk procedure, laryngocele excision, nasopharyngeal cancer, or thyroid surgery [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An adequate training improves TORS indications, skills surgical and oncological outcomes, which are important points to increase the surgeon satisfaction and motivation in the use of a new procedure. According to the literature, the most accepted indications of TORS remain cT1‐T2 and selected cT3 oropharyngeal and supraglottic cancers, 3 , 5 , 18 tongue‐base surgery (sleep apnea and unknown primary head and neck cancer), 19 , 20 and, particularly in Asia, thyroid surgeries. 21 In the present survey, we observed that the theoretical TORS indications reported by TORS surgeons were closer to the literature indications compared to non‐TORS surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The reported mean length of stay varied between 1.4 and 6.3 days [27]. It should be noted that TORS TBM results in significantly less acute morbidity than therapeutic base of tongue TORS, with OR of 0.39 (P ¼ 0.081) of moderate/severe dysphagia as determined by DIGEST overall scores for TBM compared with resection for a primary [28].…”
Section: Complications Of Transoral Surgerymentioning
confidence: 98%